2018
DOI: 10.5617/nordina.2676
|View full text |Cite
|
Sign up to set email alerts
|

A science teacher’s complex beliefs about nature of scientific inquiry

Abstract: One major concern relating to teaching scientific inquiry is that many teachers show epistemologically naive beliefs about nature of science (NOS). In this study, we use in-depth interviews to identify an upper secondary science teacher's beliefs about NOS and scientific inquiry in school. We found that what seemed to be a teacher's positivist position was embedded in broader concerns regarding pedagogical considerations and personal engagement relating to the students. This broader ecology of a teacher's beli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 30 publications
0
4
0
1
Order By: Relevance
“…Literature shows that the knowledge about SI and SPs are not translated into instructional practices easily (Bjønness & Knain, 2018;, which requires understanding of these components during the years of teacher training by the help of explicit inquiry-based instructional activities and engaging in pedagogical inquiry activities (Cigdemoglu and Koseoglu, 2020;Choi et al, 2019). Another study that is consistent with our findings, conducted by Mesci, Çavuş-Güngören, and Yesildag-Hasancebi (2019), found that PSSTs' views that all scientific investigations begin with a question (SI 1), and there is no single methodology (SI 2) improved, whereas their understanding that inquiry procedures are guided by the question (SI3), same procedures may not get the same results (SI 4), inquiry procedures influence the results (SI 5), and conclusions are drawn from data (SI 6) were not changed significantly throughout a science laboratory course including 5E-based lesson planning.…”
Section: Discussion Of Vasi Resultsmentioning
confidence: 99%
“…Literature shows that the knowledge about SI and SPs are not translated into instructional practices easily (Bjønness & Knain, 2018;, which requires understanding of these components during the years of teacher training by the help of explicit inquiry-based instructional activities and engaging in pedagogical inquiry activities (Cigdemoglu and Koseoglu, 2020;Choi et al, 2019). Another study that is consistent with our findings, conducted by Mesci, Çavuş-Güngören, and Yesildag-Hasancebi (2019), found that PSSTs' views that all scientific investigations begin with a question (SI 1), and there is no single methodology (SI 2) improved, whereas their understanding that inquiry procedures are guided by the question (SI3), same procedures may not get the same results (SI 4), inquiry procedures influence the results (SI 5), and conclusions are drawn from data (SI 6) were not changed significantly throughout a science laboratory course including 5E-based lesson planning.…”
Section: Discussion Of Vasi Resultsmentioning
confidence: 99%
“…When teachers apply inquiry in a classroom, it changes their attitudes, reduces their anxiety and they seem to recognize that inquiry is motivating for the students (Ahokoski, Korventausta, Veermans, & Jaakkola, 2017;Silm, et al, 2017). Teachers are often engaged in the inquiry approach, but they still have difficulties applying the practices to local needs (De Vries, Schouwenaars, & Stokhof, 2017) -something which is in accordance with a recent research by Bjøness and Knain (2018) that the teachers' conceptions of inquiry were not consistent with those observed in practice.…”
Section: Inquiry Approach and Teachers' Experiences Of Inquiry-based mentioning
confidence: 55%
“…For greater skill development, several interventions need to be implemented. The existing literature highlights that the understanding of scientific inquiry (SI) and science practices (SPs) does not seamlessly transition into practical teaching methods [39,40]. This underscores the need for a comprehensive understanding of these elements throughout teacher training.…”
Section: Discussionmentioning
confidence: 99%